Effects of particle size and color on photocuring performance of Si3N4 ceramic slurry by stereolithography. Issue 4 (April 2021) - Liu, Yao; Zhan, Lina; Wen, Lei; Cheng, Lin; He, Yu; Xu, Biao; Wu, Qiumei; Liu, Shaojun
Abstract: Due to high absorbance of UV light and low solid loading, the stereolithography-based additive manufacturing of gray-colored and dense Si3 N4 ceramic is of significant difficulty and challenge. The effects of geometric properties of ceramic powders on the curing performance were investigated by studying the absorption difference of the Si3 N4 ceramic particles with different colors and particle sizes and ultraviolet light. The results show that the transmission of ultraviolet light and curing performance of the darker Si3 N4 ceramic slurry are much poor. Under the same particle size, the Si3 N4 ceramic slurry using lighter particles presents the smaller scattering coefficient. The scattering coefficient (∼202) of the gray powder with ∼0.8 μm average particle size is the smallest. Under the same color, the larger the particle size, the smaller the scattering coefficient. The smallest scattering coefficient of the white powder with ∼2.0 μm average particle size is ∼110.